Marianne von Werefkin - pioneer of expressionism - Bormann, Beatrice von 1968-; Folini Ceccarelli, Mara; Ikemura, Leiko 1951-; Zieglgänsberger, Roman 1972- (Waanders Publishers, 2024)
"Marianne von Werefkin played a key role in the development of expressionism in the early 20th century, thanks to her knowledge of the latest developments in Paris. She brought this to Germany and later Switzerland and developed a unique way of painting herself, using rhythm and colour to convey her vision and emotions. Social themes, such as the lives of workers and women, remained of great importance to her. Werefkin was at the cradle of several artists' networks, such as Der Blaue Reiter, which included her partner Alexej von Jawlensky as well as Wassily Kandinsky, Franz Marc and Gabriele Münter. Museum De Fundatie is the only museum in the Netherlands to have a work by Werefkin in its collection and, with this book, offers an overview of her colourful universe for the first time in the Netherlands. Several essays give a multifaceted impression of the life, work and significance of one of the greatest art innovators of the last century."--Back cover
Colofon: This book is published to accompany the exhibition "Marianne von Werefkin - Pioneer of Expressionism" in Museum de Fundatie Zwolle from 5 October to 16 March 2025
Keywords: Werefkin, Marianne von -- 1860-1938; Werefkin, Marianne / 1860-1938 / Exhibitions; Expressionism (Art) / Exhibitions; Ausstellungskatalog -- Museum de Fundatie -- 05.10.2024-16.03.2025 -- Zwolle; Bildband